From meltdown to showdown? Challenges and options for governance in the Arctic - Humrich, Christoph; Wolf, Klaus Dieter (Frankfurt am Main, 2012)
"For several years now climate change, the hunger for raw materials, and geostrategic interests have once again moved the allocation of sovereignty and exploitation rights in the Arctic back to the foreground. In this PRIF report the authors present in search of a promising political organizational model for the Arctic region, various scenarios for how Arctic governance might look one day. The authors favor a model of integrated multi-level governance and present measures demonstrating how this model could be implemented." (author's abstract) "Klimawandel, der Hunger nach Rohstoffen und geostrategische Interessen rücken die Frage nach der Aufteilung der Souveränitäts- und Nutzungsrechte in der Arktis seit einigen Jahren wieder in den Vordergrund. Auf der Suche nach einem zukunftsträchtigen politischen Ordnungsmodell für die arktische Region präsentieren die Autoren in diesem PRIF Report verschiedene Szenarien, wie arktisches Regieren in Zukunft aussehen könnte. Sie votieren für das Modell eines integrierten Mehrebenenregierens und stellen Maßnahmen vor, wie es verwirklicht werden könnte." (Autorenreferat) begutachtet reviewed Unknown